Assessing lean deployment in healthcare - a critical review and framework - Guimarães, C.; Crespo de Carvalho, J. (Journal of Enterprise Transformation, 2014)
This article presents a critical review of lean assessment in manufacturing and service settings as a base for development of a lean assessment framework for healthcare organizations, aiming to help them throughout a long journey. Having as starting point lean projects’ failures in four public hospitals, the authors discover the lack of monitoring (among other reasons) as the main issue. This article proposes a monitoring instrument for preventing returns to the comfort zone and guiding the lean journey. The healthcare lean assessment (HLA) can be used as an “as is” diagnosis tool, assessing whether each process should be improved, disrupted, or eliminated and also as an ongoing implementation assessment, providing control measures and correction actions. Although the framework proposed requires empirical testing in further research for universal application, it can help healthcare organizations by providing a transformation roadmap and monitoring instrument and also contributes to the growing stream of academic research in this area.